Pengaruh Honeycomb Sandwich terhadap perilaku perambatan retak lelah AL 2024-t3 pada beban lebih tunggal. - Perpustakaan UGM, i-lib ([Yogyakarta] : Fac. of Geography Gadjah Mada Univ., 2001)
This research investigated the effect of the honeycomb sandwich on the characteristic of fatigue crack growth rate of aluminum alloy Al 2024-T3. Firstly, the test was carried out under sinusoidal loads with constant amplitude at the stress ratio (R) of 0,3 and 0,6. Secondly, similar to the first test, however, it was followed by a single tension overload with the overload ratio (OLR) of 1,5 and 2,0. Application of the overload was conducted manually at a static load after the crack propagated approximately 4,0 mm length. The experimental result shows that the fatigue crack growth rate are retarded when it reached honeycomb side. The honeycomb sandwich has lower the fatigue crack growth rate compared to the base material. The existence of a single overload can delay crack growth, and the increase of the overload ratio can decrease the crack growth rate. The effect of the stress ratio can decrease the crack growth rate for higher stress ratio.